2011
DOI: 10.3991/ijoe.v7i2.1394
|View full text |Cite
|
Sign up to set email alerts
|

Are Remote Labs Worth the Cost? Insights From a Study of Student Perceptions of Remote Labs

Abstract: Remote online laboratories enable students to conduct scientific investigations using real experimental equipment. However, scaling up remote labs may require significant costs in purchasing and maintaining expensive equipment compared to scaling simulated labs. While these costs are a consequence of using physical equipment, we argue that there are unique educational advantages to remote labs. This paper presents the results of a preliminary study of student perceptions of a remote lab in comparison to an ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
(12 reference statements)
1
13
0
1
Order By: Relevance
“…Online laboratories, whether remote or virtual, are another promising innovation to enhance the teaching and learning of STEM at all levels of education. Virtual online laboratories allow students to simulate scientific experiments while remote ones allow students to use real laboratory equipment from a distance through the Internet (Jona et al, 2011;Tasiopoulou and Schwarzenbacher, 2011).…”
Section: Online Laboratoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Online laboratories, whether remote or virtual, are another promising innovation to enhance the teaching and learning of STEM at all levels of education. Virtual online laboratories allow students to simulate scientific experiments while remote ones allow students to use real laboratory equipment from a distance through the Internet (Jona et al, 2011;Tasiopoulou and Schwarzenbacher, 2011).…”
Section: Online Laboratoriesmentioning
confidence: 99%
“…Online laboratories may help bridge the digital divide by providing students with faster access to experimental learning at a relatively low cost (Burd, Seazzu and Conway, 2009;Flint and Stewart, 2010;Nedungadi and Raman, 2011;Jara et al, 2011;Ku, Ahfock, and Yusaf, 2011). Simulations may be less expensive than experimental hardware, although "little empirical data exists on the actual costs of providing online laboratory access at scale" (Jona et al, 2011).…”
Section: Online Laboratoriesmentioning
confidence: 99%
“…The iLab Network, [3][4] a project based at the Office for STEM Education Partnerships at Northwestern University that seeks to put remote labs and appropriate curricula online for high school science courses, features a remote radioactivity lab housed and run at the University of Queensland in Australia. What is remarkable, however, is that using the Internet, in a matter of about 10 minutes, a high school teacher or student can set experimental parameters for a number of different distances between a strontium-90 source and Geiger counter, the number of trials at each distance, and the time for collecting counts for each trial (see Fig.…”
mentioning
confidence: 99%
“…Indeed, use of a simulation provides its own set of unique advantages [8]. Nevertheless, there is evidence that many instructors would take a well-designed remote laboratory (if such is available) over a simulation.There are justifications for this preference.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is evidence that many instructors would take a well-designed remote laboratory (if such is available) over a simulation.There are justifications for this preference. For example, [8] concluded that "the interaction with real equipment and real data in remote labs affords for more authentic inquiry, trustworthiness of data, a greater personal investment, a sense of presence and reality, and a stronger preference for remote labs than performing a similar experiment with simulated data".…”
Section: Introductionmentioning
confidence: 99%